Towards Phage Therapy: Characterization of Clostridioides difficile Bacteriophages from a South African Strain Collection - Golding, Cara (Department of Pathology, 2025)
Clostridioides difficile infection is a worldwide public health concern that affects persons with gastrointestinal dysbiosis, notably hospitalised patients on antibiotic therapy and those with other types of gastrointestinal conditions. This opportunistic infection is caused by a Grampositive, spore-forming bacillus, with conditions including diarrhoea, pseudomembranous colitis, and toxic megacolon. Antibiotic resistance has been reported for the standard of care antibiotics, while newer drugs are too costly for resource-limited clinical settings. Faecal microbiota transplantation (FMT) is highly effective but may pose a risk to immunocompromised individuals. Phage therapy is being increasingly investigated as a therapy option, notably for persons who cannot receive FMT. However, the host and regional specificity of C. difficile phages must first be characterised to ensure the correct phage cocktail is used for therapy. Although C. difficile phages have been described in other parts of the world, analysis of local South African strains has not been conducted prior to this study. This project aimed to isolate and characterise phages from a stored collection of South African C. difficile isolates, focusing on ribotype 017, which has been identified in Western Cape hospitalised patients with tuberculosis. Using a bioinformatic approach, we extracted phage genomes from previously generated C. difficile genome assemblies, assessed genomic relatedness, organised phage genomes into functional modules, and identified host defence systems. Phage induction was done using mitomycin C in liquid cultures and plaque overlay assays. Attempts were made to purify phages and generate PCR amplicons for sequence confirmation. The results of this study demonstrate the presence of phages in local C. difficile isolates and provide evidence for their classification as Caudoviricetes. Further studies are needed to determine the specific taxonomy, since recent updates have rendered previous morphology-based classification of phages inadequate.